Clinical and Experimental Characteristics of Amizon and Experience of its Use in Clinical Practice - Yu.V. Marushko; Ye.Ye. Sabadash (Zaslavsky O.Yu., 2015)
The analysis of the data on the study of Amizon is presented in this article. Information about its properties obtained during experiments in vitro and clinical investigations is provided. Pharmacodynamic and clinical features of its action in patients suffering from influenza and acute respiratory viral infection were analyzed.